(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Health workers as Human Resources (HR) in carrying out health services in hospitals are an important resource and are much needed to achieve optimal performance. There are several things that affect employee morale, one of which is the democratic leadership style and the physical work environment. This study aims to determine the effect of democratic leadership style and physical work environment on morale. Research This research was conducted directly in the Inpatient Room of Udayana Tk II Hospital. With a total sample of 70 respondents who are all nurses in the Inpatient Room of the Tk Hospital. II Udayana. Data collection is done by observation, interviews, questionnaires, documentation and literature. This study uses saturated sampling techniques and data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, determination analysis, F test analysis (F test) and T test (T test). Results showed that democratic leadership style had a positive and significant effect on morale with a t-value of 2.999 and a significant value of 0.004, the physical work environment had a positive and significant effect on morale with a t-value of 2.349 and a significant value of 0.022.